Rev activates expression of the human immunodeficiency virus type 1 vif and vpr gene products. - Garrett, E D (J Virol, 1991)
The proteins encoded by human immunodeficiency virus type 1 (HIV-1) can be divided into two temporally regulated classes. Early gene products are encoded by multiply spliced mRNA species and are expressed constitutively. In contrast, late proteins are encoded by a class of unspliced or singly spliced viral transcripts whose cytoplasmic expression is induced by the viral Rev trans activator. Here, we demonstrate that the viral Vif and Vpr proteins are encoded by singly spliced viral mRNAs whose expression is activated by Rev. This activation is shown to result from the reduced utilization of splice sites adjacent to or within the vif and vpr coding sequences. Vif and Vpr therefore belong to the class of late HIV-1 gene products. IMAGES: